Taking on the Traditions in Philosophy of Education: A Symposium - Burns, David P.; Chinnery, Ann; Ruitenberg, Claudia W.; Waddington, David I. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2009)
In this symposium, we highlight the importance of critical engagement with philosophical traditions in philosophy of education. On one hand, it is important to critique the exclusionary nature of canons of knowledge that have shaped both philosophy and education; on the other, we believe it is important to acknowledge that our thinking, as well as the thinking of philosophers of education before us, is undeniably and indelibly marked by these traditions. Framed by Jacques Derrida’s reflections on the “figure of the philosopher” and Michael Naas’s conception of “taking on the tradition,” David Burns invites us to revisit the Stoic conception of character as a counterpoint to current discourses of character education in Canadian schools; David Waddington examines how Thomas Jefferson’s writings influenced John Dewey’s conception of democracy and democratic education; and Ann Chinnery proposes acknowledgement of intellectual indebtedness as an essential scholarly disposition, looking specifically at the “difficult inheritance” of Emmanuel Levinas’s debt to Martin Heidegger.